Angioembolization in intra-abdominal solid organ injury: Does delay in angioembolization affect outcomes?. Issue 4 (October 2020) - Chehab, Mohamad; Afaneh, Amer; Bible, Letitia; Castanon, Lourdes; Hanna, Kamil; Ditillo, Michael; Khurrum, Muhammad; Asmar, Samer; Joseph, Bellal
Abstract : INTRODUCTION: Angioembolization (AE) is an integral component in multidisciplinary algorithms for achieving hemostasis in patients with trauma. The American College of Surgeons Committee on Trauma recommends that interventional radiologists be available within 30 minutes to perform emergent AE. However, the impact of the timing of AE on patient outcomes is still not well known. We hypothesized that a delay in AE would be associated with increased mortality and higher blood transfusion requirements in patients with blunt intra-abdominal solid organ injury. METHODS: A 4-year (2013–2016) retrospective review of the ACS Trauma Quality Improvement Program database was performed. We included adult patients (age, ≥18 years) with blunt intra-abdominal solid organ injury who underwent AE within 4 hours of hospital admission. Patients who underwent operative intervention before AE were excluded. The primary outcome was 24-hour mortality. The secondary outcome was blood product transfusions. Patients were grouped into four 1-hour intervals according to their time from admission to AE. Multivariate regression analysis was performed to accommodate patient differences. RESULTS: We analyzed 1, 009, 922 trauma patients, of which 924 (1 hour, 76; 1–2 hours, 224; 2–3 hours, 350; 3–4 hours, 274) were deemed eligible. The mean ± SD age was 44 ± 19 years, and 66% were male. The mean ± SD time to AE was 144 ± 54 minutes, and 92% of patients underwent AE more than 1 hour after admission. Overall 24-hour mortality was 5.2%. On univariate analysis, patients receiving earlier AE had decreased 24-hour mortality ( p = 0.016), but no decrease in blood products transfused. On regression analysis, every hour delay in AE was significantly associated with increased 24-hour mortality ( p < 0.05). CONCLUSION: Delayed AE for hemorrhagic control in blunt trauma patients with an intra-abdominal solid organ injury is associated with increased 24-hour mortality. Trauma centers should ensure timeliness of interventional radiologist availability to prevent a delay in vital AE, and it should be a focus of quality improvement projects. LEVEL OF EVIDENCE: Prognostic, level III.